Advancing Meaningful Inclusion Through Design: An Architecture of Dis/Ability - Friedlaender, Eron; Neilson, Stuart; Carpenter, Jennifer; Verona, Irina (MAJ - Malaysia Architectural Journal, 2025)
We heard a call to action after presenting at the 2023 World Congress of Architects in the stunningly creative city of Copenhagen: take notice of the “limiting virtues” of our built environment! As a successful interprofessional team representing public health, architecture, art, and neurodivergent communities, we demonstrate the potential of a collaborative approach to meaningful inclusion through a series of exemplar projects. This work relies on imagination, respect for genuine end-user engagement, and developing a common working language across the arts and sciences. Our approach demonstrates independence from traditional applications of accessible design in our investigation and exploration of novel tools to measure the impact of interventions, appreciation for the myriad ways in which built and natural environments relate to public health, community mobility, and independence as well as commitment to teach this as a new academic discipline. Our complementary lenses to the operationalization of accessible design challenge the traditional owners of this work to consider the true meaning of inclusion with thoughtfully articulated intended outcomes. We are informed by end-user need, aim to apply methodologic rigor in post-occupancy surveys with dedicated resources for iterative change based on the outcome, and employ genuine partnership with members of vulnerable and disabled populations not yet fully represented in the design process. This approach respects the value of diversity within public spaces with intentional consideration of design choices that magnify social exclusion and the cascade of loss that follows avoidance and lost opportunity. Locating affordances, acknowledging limitations, and making way for multimedia, multimodal communication from largely “unheard” and unacknowledged autistic populations anchors our collaborative approach. We encourage openness to language (both words and images) in which community members express their needs, facility in mapping the accessible environment, and explorations of the cognitive dissonance between disabled people and enabled people in the same spaces. We are confident there is tremendous potential to make significant progress in our collective but to date parallel efforts to advance the ways in which our built environment may be modified to support more successful and rewarding access by more people in more locations.